Application of Image Media to Improve Elementary School Students' Vocabulary Mastery - Rahayu, Arum Putri (Jurnal Paradigma, 2023)
This research is rooted in low vocabulary mastery in elementary school students. In understanding English lessons students often have difficulties due to their low mastery of vocabulary. Limited face-to-face time in class and foreign English is one of the reasons for the lack of successful learning activities. This study aims to observe the success of the application of image media in improving vocabulary mastery of grade IV students of SDN Girimulyo I. The subjects of this study were 17 students and English teachers and were carried out using the PTK method. The research lasted for two cycles and the successful application of image media in improving students' vocabulary mastery was carried out well. In obtaining research data, researchers use research instruments in the form of observation and interview guidelines. Furthermore, the data obtained is then processed and analyzed using qualitative descriptive analysis. The results showed that the application of the use of image media in vocabulary learning in the school was satisfactory.